Determination of the bonding strength in solid oxide fuel cells' interfaces by Schwickerath crack initiation test. Issue 11 (September 2017) - Boccaccini, D.N.; Sevecek, O.; Frandsen, H.L.; Dlouhy, I.; Molin, S.; Charlas, B.; Hjelm, J.; Cannio, M.; Hendriksen, P.V.
Abstract: An adaptation of the Schwickerath crack initiation test (ISO 9693) was used to determine the bonding strength between an anode support and three different cathodes with a solid oxide fuel cell interconnect. Interfacial elemental characterization of the interfaces was carried out by SEM/EDS analysis on fracture surfaces to investigate the bonding mechanisms. SEM/EDS of fresh fractures were also performed to determine the cohesion/adhesion mechanism of bonding. Calculations of the residual stresses were determined by finite element simulation using ANSYS, based on thermo-mechanical properties of the materials obtained by measurement, calculation or literature.